Cardiac and renal protective effects of urate-lowering therapy. (19th December 2017) - Richette, Pascal; Latourte, Augustin; Bardin, Thomas
Abstract: Patients with gout often have co-morbidities such as cardiovascular disease, renal failure and metabolic syndrome components. Some studies, but not all, have suggested that hyperuricaemia and gout are associated with increased risk of myocardial infarction, renal failure and death primarily because of increased risk of cardiovascular events. Therefore, knowledge of the effects of urate-lowering therapy (ULT) on co-morbidities, in particular cardiovascular events and chronic kidney disease, is crucial. Randomized controlled trials (RCTs) have suggested that allopurinol, a xanthine oxidase inhibitor, could improve exercise capacity in patients with chronic stable angina and could decrease blood pressure in adolescents. In contrast, a well-designed RCT found no effect of allopurinol in patients with heart failure. The impact of ULT in patients with chronic kidney disease is unclear. Some RCTs found that allopurinol could slow the decline in kidney function, whereas a recent controlled trial found no benefit of febuxostat. Large randomized placebo-controlled trials are warranted to confirm or not the benefit of ULT on co-morbidities.